Performance assessment of a hybrid complementary power system for sustainable electrification: a case study - Konneh, Keifa Vamba; Masrur, Hasan; Othman, Mohammad Lutfi; Senjyu, Tomonobu (Elsevier BV, 2022)
This paper looks at an islanded complementary power system in Sierra Leone’s South-eastern region. It presents a method for assessing or evaluating the performance of an existing complementary hybrid energy system (Bo-Kenema power network) in an urban environment, taking seasonal variability into consideration. The proposed method attempts to assess the feasibility of establishing either a new hybrid system without current sources or a hybrid system that includes both existing and new sources. A comprehensive techno-economic-environmental optimization analysis was carried out in which 13 scenarios were evaluated and compared. With a net present cost (NPC) of $50.4 million (M) and a cost of energy (COE) of $0.211/kWh, Case 1 (Solar photovoltaics (PV)/generator 1 (G1)/generator 2 (G2)/generator 3 (G3)/battery/hydro/converter) was found to be the most cost-effective and sustainable scenario. The sensitivity analysis performed on Case 1 (optimum scenario) revealed that the total system cost was heavily reliant on turbine efficiency, PV and battery capital prices. Furthermore, adding two extra high-efficiency turbines (75%) to the optimum scenario eliminated the PV component and reduced the COE and NPC by 38.9% (from $0.211/kWh to $0.129/kWh) and 39.1% (from $50.4M to $30.7M) respectively, while increasing CO2 emissions by 49.9%. This elimination led to a change in the configuration of Case 1 (G1/G2/G3/hydro). The preference of the governing authorities determines whether the previous or later optimal design is to be implemented. By implementing this strategy, the optimum scenario can provide cost-effective and long-term electricity for the selected region.